Evaluasi Pemanfaatan Teknologi Informasi Pada Matakuliah Jaringan Komputer di Era Pandemi Covid-19 - Elfizar Elfizar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The Covid-19 pandemic makes massive use of information technology (IT) in various fields. This study aims to evaluate the use of IT in Computer Networks lectures at the Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Riau in the era of Covid-19 Pandemic. This causal comparative study uses data from the results of student achievement in the Even Semester Academic Year 2019/2020. There are two lecture models given to students namely synchronous and asynchronous models. The use of the model is based on the type of lecture material provided. Furthermore, the results of student achievement obtained at the end of the semester are compared with the results of student achievement in the previous year that used physical face-to-face lectures. The results of this study indicate that there was an increase of 7.17% in the student achievement during the use of IT in lectures during the Covid-19 Pandemic with the effective synchronous lectures duration from 60 to 100 minutes.